2016
DOI: 10.1016/j.applthermaleng.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Use of a sol-gel hybrid coating composed by a fluoropolymer and silica for the mitigation of mineral fouling in heat exchangers

Abstract: The technology of the organic/inorganic hybrid coating was employed in the preparation of a hydrophobic coating (contact angle higher than 140°) for fouling mitigation on stainless steel heat transfer surfaces. A commercial triethoxysilane perfluoropolyethers was combined with a sol-gel silica network with the aim to increase the mechanical and thermal resistance of the films when exposed to aggressive liquid environments as the heat exchanging fluids. The experimentation on a shell and tube heat exchanger pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…This result indicates that there is no induction period for PS and there are different induction periods for each Fe-Al MNS sample, which is similar to previous research [32]. Bogacz [33] found that there was a significant influence between the wettability of the heat-transfer surface and the fouling adhesion, which was more significant than the influence of roughness. For the heat-transfer surface with the lower contact angle, the lower removal rate appeared for the deposited fouling on the surface [34,35].…”
Section: Antifouling Property Of Fe-al Mns Samplesupporting
confidence: 89%
“…This result indicates that there is no induction period for PS and there are different induction periods for each Fe-Al MNS sample, which is similar to previous research [32]. Bogacz [33] found that there was a significant influence between the wettability of the heat-transfer surface and the fouling adhesion, which was more significant than the influence of roughness. For the heat-transfer surface with the lower contact angle, the lower removal rate appeared for the deposited fouling on the surface [34,35].…”
Section: Antifouling Property Of Fe-al Mns Samplesupporting
confidence: 89%
“…In the last few years, the literature reported on this type of coatings increased notably [60,[291][292][293][296][297][298][299]. Numerous techniques and methods have been used in the development of superhydrophobic surfaces [300][301][302], and the sol-gel process, as the versatile method that it is, was no exception [294,299,[303][304][305][306][307]. Recently, a very detailed and comprehensive review, focused on the latest developments of superhydrophobic coatings for corrosion mitigation, has been published [308].…”
Section: Coatings With Superhydrophobic Functionmentioning
confidence: 99%
“…The SCA copolymerizes with the functional polymer through reactions with these bonds to give [polymer]–X–Si­(−R) n (−OH) 3– n . In comparison to hydrocarbons as polyethylene R–(CH 2 –CH 2 −) m , fluorocarbons such as perfluoroalkyl R–(CF 2 −) m and poly­(vinylidene difluoride) R–(CF 2 –CH 2 −) m show high hydrophobicity and abrasion resistance, when used as polymers. The flexibility of the polymer increases when an ether group is included, such as perfluoropolyether R–((CF 2 −) 3 O−) m . …”
Section: Introductionmentioning
confidence: 99%